Spherical Silica Particles
By employing a hydrothermal treatment process with an alkaline aqueous silica solution, the production of spherical silica particles with fine voids addresses the challenges of particle strength and size, resulting in enhanced reliability and structural integrity for use in electronic materials.
Patent Information
- Application Number
- JP2024543669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-08-30
AI Technical Summary
Existing methods for producing hollow silica particles face challenges such as reduced particle strength with increased hollow ratio, exposure of large internal voids during via processing, and difficulty in achieving small particle sizes.
The production of spherical silica particles with fine voids using an alkaline aqueous silica solution, involving a hydrothermal treatment process with specific conditions to control void formation and maintain particle strength.
The resulting spherical silica particles have smaller voids, enhanced strength, and improved reliability for use as fillers in electronic materials, with the ability to maintain structural integrity under pressure.
Smart Images

Figure 0007657375000004 
Figure 0007657375000005 
Figure 0007657375000006
Abstract
Description
[Technical field]
[0001] The present invention relates to spherical silica particles and a method for producing the same, and more particularly to hollow spherical silica particles having internal voids and a method for producing the same. [Background technology]
[0002] Wet template methods are known as a method for producing hollow silica. These include a method in which inorganic particles other than silica are coated on a template and the inside is dissolved or decomposed by heating (Patent Documents 1 and 2), and a method in which silica is synthesized in a solution in which a hydrophobic organic solvent is emulsified in a hydrophilic solvent (Patent Documents 3 and 4). Another method for producing hollow silica is to melt porous silica to produce hollow silica (Patent Document 5). Also known are methods for producing hollow silica by spray drying and spray pyrolysis (Patent Documents 6 and 7). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-140286 A [Patent Document 2] International Publication No. 2022 / 014130 [Patent Document 3] JP 2014-55082 A [Patent Document 4] International Publication No. 2019 / 131658 [Patent Document 5] JP 2010-260755 A [Patent Document 6] Patent No. 7008004 [Patent Document 7] JP 2020-83736 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the methods disclosed in Patent Documents 1 to 3 result in a structure with large voids inside the particles, and increasing the hollow ratio tends to reduce the particle strength. When used as a filler for electronic materials, the large internal voids are exposed during via processing, posing problems such as plating reliability. In the method disclosed in Patent Document 4, since the operation of melting the porous silica is performed, it is difficult to obtain particles having a particle size of 3 μm or less. Similarly, in the methods disclosed in Patent Documents 5 and 6 using spray drying, it is also difficult to produce particles having a particle size of 5 μm or less. The present invention has been completed in view of the above-mentioned circumstances, and an object of the present invention is to provide novel spherical silica particles and a method for producing the same. [Means for solving the problem]
[0005] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that spherical silica particles having fine voids therein can be produced using an alkaline aqueous silicic acid solution (hereinafter referred to as "alkaline aqueous silicic acid solution") as a raw material, and based on this finding, they completed the following invention. That is, the spherical silica particles of the present invention are mainly composed of silica, have an average particle size of 0.1 to 10.0 μm, and a true specific gravity measured with nitrogen gas of 0.9 to 1.9 g / cm 3 The pore volume is 0.1 mL / g or less, the Na content is 10 ppm or less, the true specific gravity retention rate measured with nitrogen gas before and after pressurization at 300 MPa for 1 minute is 80% or more, and for each particle, the ratio of particles whose maximum major axis of the internal void is half or more of the major axis of the particle is 60% or less. The method for producing spherical silica particles of the present invention, which solves the above-mentioned problems, comprises the steps of: preparing a raw silica particle dispersion from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of a basic substance consisting of at least one of a quaternary ammonium salt and a base having a cyclic amidine structure; a hydrothermal treatment step of replacing the dispersion medium for dispersing the raw silica particles in the dispersion with water, and then pressurizing and heating the mixture to 130° C. or higher and 250° C. or lower to obtain a dispersion of hydrothermally treated raw silica particles; a heating step of heating the dispersion liquid or the raw silica particles obtained by solid-liquid separation from the dispersion liquid after the hydrothermal treatment step to remove organic matter contained in the dispersion liquid and prepare spherical silica particles; having The mixed solvent has a relative dielectric constant of 21 or more and 40 or less, The quaternary ammonium derived from the basic substance is blended in a molar ratio of 0.3 to 0.8 relative to the silicon element derived from the silicic acid. Effect of the Invention
[0006] The spherical silica particles of the present invention are particles having finer voids than conventional spherical silica particles having voids inside. Conventional spherical silica particles having large voids inside the particles have shells that are easily destroyed by external forces, but the spherical silica particles of the present invention have finer voids than conventional particles and are therefore less likely to be destroyed even when a similar external force is applied. [Brief description of the drawings]
[0007] [Figure 1] 1 is a histogram showing particle size distributions of test samples of Test Examples 4, 5, 9, and 11 in the Examples. [Diagram 2] 1 is a SEM photograph of a test sample of Test Example 3 in the Examples. [Diagram 3] 1 is a SEM photograph of a test sample of Test Example 4 in the Examples. [Figure 4] 1 is a SEM photograph of a test sample of Test Example 5 in the Examples. [Diagram 5] 1 is a SEM photograph of a test sample of Test Example 6 in the Examples. [Figure 6] 1 is a SEM photograph of a test sample of Test Example 7 in the Examples. [Figure 7] 1 is a SEM photograph of a test sample of Test Example 9 in the Examples. [Figure 8] 1 is a SEM photograph of a test sample of Test Example 11 in the Examples. [Figure 9] 1 is a SEM photograph of a test sample of Test Example 13 in the Examples. [Figure 10] 1 is a SEM photograph of a test sample of Test Example 16 in the Examples. [Figure 11] 1 is a SEM photograph of a test sample of Test Example 17 in the Examples. [Figure 12] 1 is a SEM photograph of a test sample of Test Example 18 in the Examples. [Figure 13] 1 is a SEM photograph of a test sample of Test Example 19 in the Examples. [Figure 14] 1 is a cross-sectional TEM photograph of a test sample of Test Example 17 in the Examples. [Figure 15] 1 is a cross-sectional SEM photograph of a test sample of Test Example 11 in the Examples. [Figure 16] 1 is a cross-sectional SEM photograph of a test sample of Test Example 17 in the Examples. [Figure 17] 1 is a cross-sectional SEM photograph of a test sample of Test Example 22 in the Examples. [Figure 18] 1 is a cross-sectional SEM photograph of a test sample of Test Example 23 in the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The spherical silica particles and the method for producing the same of the present invention will be described in detail below with reference to the following embodiments.
[0009] (Spherical silica particles) The spherical silica particles of this embodiment have voids inside and are particles with high sphericity. The spherical silica particles are mainly composed of silica, specifically, 50% or more of the total mass is composed of silica, and the lower limit of the silica composition ratio is 60%, 70%, 80%, 90%, 95%, or 99%, and it is particularly preferable that the silica content is 100% and that the silica content is 100% without containing anything other than unavoidable impurities. When a substance other than silica is contained, it can be contained in the form of particles inside the spherical silica particles of this embodiment, or it can be dispersed at the atomic level inside the spherical silica particles.
[0010] The particle size of the spherical silica particles is 0.1 to 10 μm, and in particular, the upper limit value can be 7 μm, 5 μm, 3 μm, or 2 μm. The sphericity of the spherical silica particles is not particularly limited, but is preferably 0.9 or more, and more preferably 0.95 or more.
[0011] The spherical silica particles of the present embodiment are so-called hollow particles. Here, the spherical silica particles are said to be hollow when the particle density is 1.9 g / cm 3 Specifically, this means that the g / cm 3 Below that, 1.6g / cm 3 The lower limit of the density is preferably 0.9 g / cm. 3 and 1.1 g / cm 3 , 1.2g / cm 3 It is preferable that:
[0012] In measuring the density of particles, the volume of the particles is measured by the constant volume expansion method using nitrogen. The volume measured includes voids into which nitrogen gas cannot penetrate, and spherical silica particles that have such voids and have a particle density within the above range are called hollow particles. The voids present inside the particles may be one or multiple.
[0013] In the spherical silica particles of this embodiment, the ratio of particles having an internal void with a maximum major axis of at least half the major axis of the particle is 60% or less. The major axis of the internal void and the major axis of the particle are values measured on a cross section of the spherical silica particles embedded in a resin.
[0014] In other words, the long diameter of the cut surface of a particle is taken as the long diameter A of that particle, and if the long diameter B of one or more of the cross sections of the internal voids that appear in that cross section is half or more of A, it is determined that there is a "particle whose internal voids have a maximum long diameter that is equal to or greater than half of the particle's long diameter." Even if multiple internal voids with B being half or more of A are found in a single spherical silica particle, there is only one "particle whose internal voids have a maximum long diameter that is equal to or greater than half of the particle's long diameter."
[0015] Ten particles are randomly selected for measurement (100 particles may also be used). The abundance ratio can be calculated from the number of particles out of the 10 particles (100 in the case of 100 particles) that have "particles whose maximum major axis of the internal void is equal to or greater than half the major axis of the particle itself."
[0016] The inside of the spherical silica particles is preferably porous with many fine voids. It is particularly preferable that the particles have fine voids. When the inside of the particles is porous, it is preferable that the particle has a denser structure near the surface and that the pores near the center are relatively large.
[0017] For example, in the spherical silica particles of this embodiment, it is preferable that the average porosity of the central region in the cross section of the particle is 5% or more and 90% or less, and the average porosity of the outer shell region, which is the other region, is less than the average porosity of the central region and is 2% or more and 80% or less.
[0018] The average porosity of the central region may preferably be 10%, 20%, or 30% as a lower limit, and 80%, 70%, or 50% as an upper limit. These upper and lower limits may be combined in any desired manner.
[0019] The average porosity of the outer shell region may preferably be 3%, 4%, or 5% as a lower limit, and 80%, 70%, or 60% as an upper limit. These upper and lower limits may be combined in any desired manner.
[0020] The central region and the outer shell region are evaluated by comparing multiple cross sections obtained by FIB processing in 10-20 nm steps using FIB / SEM while the spherical silica particles of this embodiment are embedded in resin, and using the image of the cross section with the largest area (evaluation cross section image). Here, the central region is a circular region having a size of half the radius of the particle from the center of the particle in the evaluation cross section image. The outer shell region is the region of the particle excluding the central region. The average porosity is calculated using image processing software (e.g., A-zo-kun: manufactured by Asahi Kasei Engineering) by utilizing the difference in color of the void parts. This is performed for 10 randomly selected particles, and the average value is calculated.
[0021] It is preferable that these pores are not connected to the outside. In particular, the volume of pores connected to the outside is 0.1 mL / g or less, preferably 0.08 mL / g or less, more preferably 0.07 mL / g or less. Here, the measurement of the pore volume is performed by the BJH method using nitrogen, and the volume of pores with a diameter of 250 nm or less is measured. Here, pores that are not connected to the outside are determined by whether or not nitrogen gas can reach the pores.
[0022] The spherical silica particles of the present embodiment have void walls that are not easily destroyed by pressure. Specifically, the true specific gravity maintenance rate and the dielectric loss tangent maintenance rate are maintained within a certain range before and after application of a pressure of 300 MPa for 1 minute.
[0023] The true specific gravity retention rate is a value that indicates the percentage of the true specific gravity value before pressurization that is maintained without the voids being destroyed by pressurization. When the hollow structure is destroyed during pressurization and the voids inside are connected to the outside, the volume of the particle decreases by the volume of the voids, resulting in an increase in true specific gravity. Therefore, an increase in true specific gravity after pressurization means that the hollow structure has been destroyed by pressurization. The true specific gravity retention rate is calculated using the true specific gravity measured with nitrogen gas and the true specific gravity measured with helium gas using the following formula: (True specific gravity retention rate) = {(True specific gravity measured with helium gas) - (True specific gravity measured with nitrogen gas after pressurization test)} / {(True specific gravity measured with helium gas) - (True specific gravity measured with nitrogen gas before pressurization test)} x 100 (%)
[0024] Specifically, a true specific gravity maintenance rate of 100% means that there is no change in the value of true specific gravity before and after pressurization, and that voids are not destroyed by pressurization. A true specific gravity maintenance rate of 0% means that the value of true specific gravity after pressurization is the same as the value of true specific gravity measured with helium, and that all voids into which helium can enter are destroyed by pressurization. The true specific gravity maintenance rate is 80% or more, preferably 85% or more, and more preferably 90% or more, of the value before pressurization.
[0025] The true specific gravity after pressurization can be calculated by taking into account the true specific gravity maintenance rate of the true specific gravity before pressurization and the true specific gravity measured using helium gas, and taking the weighted average. For example, (true specific gravity after pressurization) = {(true specific gravity maintenance rate) x (true specific gravity before pressurization) + (100 - (true specific gravity maintenance rate)) x (true specific gravity measured using helium gas)} ÷ 100.
[0026] The dielectric loss tangent retention rate is calculated from the values of the dielectric loss tangent before and after the application of pressure using the following formula: (Dielectric loss tangent retention rate) = (Dielectric loss tangent after the application of pressure) / (Dielectric loss tangent before the application of pressure) x 100 (%). The dielectric loss tangent retention rate is preferably 500% or less, more preferably 400% or less, and even more preferably 300% or less. When the hollow structure of the particles is destroyed, the surfaces of the voids within the particles are exposed, and the dielectric loss tangent increases. Therefore, a large dielectric loss tangent retention rate means that destruction of the hollow structure is progressing.
[0027] The spherical silica particles of this embodiment preferably have a D90 / D10 of 2.0 to 20.0. In particular, the upper limit is preferably 18.0, 15.0, or 13.0, and the lower limit is preferably 2.2, 2.4, or 2.6. These upper and lower limits can be arbitrarily combined. Note that D10 is the particle size of the particles that are 10% by volume from the smallest particle size, and D90 is the particle size of the particles that are 90% by volume from the smallest particle size.
[0028] Furthermore, the spherical silica particles of this embodiment have a true specific gravity of 2.2 g / cm as measured using helium gas. 3 It is preferable that the content is 2.25 g / cm or more. 3 It is more preferable that the specific gravity is equal to or higher than 2.3 g / cm. Helium gas can also penetrate into voids present inside the particles, and the specific gravity of the particles without voids can be measured. Here, the specific gravity of silica is 2.3 g / cm. 3 It can be inferred that the closer the value is to this value, the lower the content of impurities other than silica.
[0029] The spherical silica particles of this embodiment can be surface-treated to introduce an organic functional group. The organic functional group to be introduced is not particularly limited, but examples include phenylamino group, amino group, vinyl group, epoxy group, phenyl group, acrylic group, methacrylic group, alkyl group, and organic functional groups having these organic functional groups at the end. Method for introducing these organic functional groups Surface treatment can be performed with a surface treatment agent having these organic functional groups in its molecular structure. Examples of the surface treatment agent include silane compounds and titanium compounds. The amount of these organic functional groups to be introduced can be appropriately selected as needed, but for example, based on the total amount of the number of organic functional groups introduced on the surface of the spherical silica particles and the number of OH groups present on the surface, about 10% to 100%, and further 30%, 50%, 60%, etc. can be adopted as the lower limit, and 90% can be adopted as the upper limit.
[0030] (Slurry Composition) The slurry composition of this embodiment has the spherical silica particles of this embodiment described above and a dispersion medium that disperses the spherical silica particles. The spherical silica particles can be those described above. The dispersion medium is liquid, and is an organic substance, water, etc. Examples of organic substances include general organic solvents and uncured monomers. Some solutes may be dissolved in the dispersion medium. The mixture ratio of the spherical silica particles and the dispersion medium is not particularly limited, but the spherical silica particles can be contained in an amount of 20% or more, further 40% or more, or 60% or more. Furthermore, other components can be contained as necessary. For example, a dispersant, etc.
[0031] (Resin composition) The resin composition of the present embodiment includes the spherical silica particles of the present embodiment described above and a resin material that disperses the spherical silica particles. The spherical silica particles can be those described above. The resin material can be a solid material after curing or a liquid material before curing. The resin material after curing can be either a thermosetting resin or a thermoplastic resin. Specific examples of the resin material include, but are not limited to, epoxy resin, phenolic resin, polyimide resin, fluororesin, polyphenylene oxide resin, and monomers and precursors thereof before curing. The mixing ratio of the spherical silica particles and the resin material is not particularly limited, but the spherical silica particles can be contained in an amount of 20% or more, further 40% or more, or 60% or more. Furthermore, other components can be contained as necessary. For example, a dispersant. The resin composition of the present embodiment can also be determined to be the above-mentioned slurry composition when the resin material is a liquid material such as a precursor.
[0032] (Method of producing spherical silica particles) The method for producing spherical silica particles of the present embodiment includes a raw silica particle preparation step, a hydrothermal treatment step, a heating step, and other steps that are adopted as necessary.
[0033] (Raw material silica particle preparation process) The raw silica particle preparation process is a process in which raw silica particles, which are the source of spherical silica particles, are precipitated from silicic acid contained in a raw solution in a mixed solvent of water and an organic solvent in the presence of a basic substance to form a dispersion. The precipitated raw silica particles are generally equivalent to the spherical silica particles produced, but contain a high content of moisture, organic matter, etc.
[0034] The precipitation of the raw silica particles is preferably carried out with stirring. The temperature during precipitation is not particularly limited, but the lower limit is 0°C, and the upper limit is 40°C, 50°C, or 60°C.
[0035] The concentration of silicic acid in the raw solution is not particularly limited, but based on the total mass, the lower limit can be 1%, 2%, 3%, or 5% in terms of oxide (SiO2: silica), and the upper limit can be 8%, 10%, 15%, or 17%. To obtain the required concentration, the solution can be diluted with water, an organic solvent, or a mixed solvent of water and an organic solvent. The oxide equivalent here is a value calculated on the assumption that all silicon elements contained are contained as oxides. The raw solution can contain other metal compounds other than silicic acid. Examples of other metal compounds that can be contained include water-soluble compounds and metal oxides with a particle size of 100 nm or less (particularly metal oxides with a particle size of 50 nm or less, 30 nm or less, or 10 nm or less). The other metal oxides can be incorporated when silicic acid precipitates and becomes particulate, forming composite oxides, etc.
[0036] In addition, the precipitation of the raw silica particles is preferably carried out in a state adjusted to a predetermined pH. The adjustment to the predetermined pH is preferably carried out by adding a basic substance or an organic acid such as acetic acid. The predetermined pH can be exemplified by lower limits of 7.0, 7.5, and 7.8, and upper limits of 10.0, 9.5, 9.0, 8.5, and 8.2.
[0037] Here, the mixed solvent has a relative dielectric constant of 21 or more and 40 or less. The upper limit of the relative dielectric constant may be 38, 35, or 33, and the lower limit may be 21.5, 23, or 25. These upper and lower limit values may be arbitrarily combined. Here, the relative dielectric constant of the mixed solvent is the relative dielectric constant calculated for the mixed solvent consisting of only the contained water and organic solvent. Specifically, it is calculated as a weighted average of the relative dielectric constant of water and the relative dielectric constant of the mixed organic solvent in terms of volume ratio.
[0038] The organic solvent is miscible with water and has a dielectric constant within the above range after mixing. Preferred organic solvents are ketones, esters, and alcohols, and in particular, acetone, methyl ethyl ketone, ethyl acetate, and the like can be used alone or as a mixture, and acetone is more preferably used. The mixing ratio of the organic solvent and water is set so that the mixed solvent has a dielectric constant within the above range.
[0039] The basic substance is at least one of a quaternary ammonium and a base having a cyclic amidine structure. Although they are not particularly limited, the quaternary ammonium is preferably selected from quaternary ammonium having 4 to 16 carbon atoms, and in particular, tetramethylammonium having 1 carbon atom, tetraethylammonium having 2 carbon atoms, and tetrabutylammonium having 4 carbon atoms can be exemplified. Quaternary ammonium usually has some anion as a counter ion. For example, tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), and tetrabutylammonium hydroxide (TBAOH) having hydroxide ions, and tetramethylammonium chloride, tetraethylammonium chloride, and tetrabutylammonium chloride having chloride ions can be exemplified. Examples of bases having a cyclic amidine structure include diazabicycloundecene (DBU) and diazabicyclononene (DBN).
[0040] The basic substance is contained in a ratio of 0.3 or more and 0.8 or less based on the number of moles of silicon element derived from silicic acid, and the lower limit can be 0.35, 0.4, and the upper limit can be 0.75, 0.7, 0.6. These upper and lower limits can be arbitrarily combined. By making the amount of basic substance added equal to or more than the lower limit, the particle size of the raw silica particles produced becomes large and aggregates are not formed, or the density of silica in the raw silica particles produced becomes high. By making the amount added equal to or less than the upper limit, oligomerization can be prevented and particle formation can be efficiently performed. If the density of silica is low, it tends to shrink when heated in the heating process described below, or the porosity of the obtained spherical silica particles when made into porous particles or hollow particles tends to be large.
[0041] The basic substance may be added to the mixed solvent before or after the silicic acid. Furthermore, the basic substance may be added in several portions rather than all at once.
[0042] The concentration of silicic acid in the raw solution is not particularly limited, but the upper limit is preferably 0.1%, 0.2%, 0.3%, or 0.4%, and the lower limit is preferably 1.0%, 1.5%, 2.0%, or 3.0%, calculated as oxide based on the mass of the raw solution. The silicic acid is preferably supplied as an alkaline silicic acid aqueous solution obtained by any one of the following methods a) to c). These steps a) to c) are preferably performed with stirring. An appropriate amount of an organic solvent or a basic substance is added to the alkaline silicic acid aqueous solution obtained by the following steps to prepare the raw solution.
[0043] a) Heating and pressurizing silicon dioxide in an aqueous solution of a basic substance. Silicon dioxide can be synthesized from metal silicon, synthesized from silicon compounds, natural products, etc. In particular, silicon dioxide synthesized from metal silicon is preferred because it is easy to obtain high-purity metal silicon as the raw material. For example, powdered silicon dioxide obtained by a method of burning metal silicon powder (the so-called VMC method) can be used. Here, by using powdered silicon dioxide, the specific surface area becomes large, and the dissolution rate in an aqueous solution of a basic substance can be increased.
[0044] The basic substance contained in the aqueous basic substance solution for dissolving silicon dioxide may be the above-mentioned basic substance as it is, or other basic substances (other basic substances) may be used. When other basic substances are used, it is preferable to remove the other basic substances by washing or ion exchange after dissolving silicon dioxide.
[0045] Silicon dioxide can be dissolved in an aqueous solution of a basic substance by increasing the boiling point of the aqueous solution of the basic substance through pressure and maintaining the temperature at or above the boiling point at normal pressure. For example, heating at 180°C while applying pressure can be used. A higher dissolving temperature can improve the dissolving speed, while a lower temperature can reduce the pressure, simplifying the dissolving equipment.
[0046] The silicon dioxide to be dissolved is preferably 17%, 15%, or 10% by weight, with the lower limit being 1%, 3%, or 5%, based on the total weight. These upper and lower limits can be combined in any way. The concentration of the basic substance in the aqueous basic substance solution is not particularly limited, but is preferably such that the basic substance has an appropriate concentration when the raw material solution is finally prepared.
[0047] b) Removal of Na ions from an aqueous sodium silicate solution in the presence of a basic substance. The sodium silicate aqueous solution can be prepared by dissolving sodium silicate in water or water glass. The basic substance can be any of the above-mentioned. By removing sodium ions from the sodium silicate aqueous solution in the presence of a basic substance, the sodium in the sodium silicate is replaced with a basic substance. The removal of sodium ions can be carried out using an ion exchange resin or the like. The sodium silicate to be dissolved is preferably set to an upper limit of 17%, 15%, or 10%, and a lower limit of 1%, 3%, or 5%, calculated as oxide based on the total mass. These upper and lower limits can be combined in any way. The concentration of the basic substance in the aqueous basic substance solution is not particularly limited, but is preferably set to a concentration that results in an appropriate basic substance concentration when the raw material solution is finally prepared.
[0048] c) Dissolution of metallic silicon in an aqueous solution containing a basic substance and / or a second basic substance. Silica is produced by immersing and dissolving metallic silicon in an aqueous solution in which the above-mentioned basic substance and / or second basic substance is dissolved. The metallic silicon is preferably in the form of powder or granules. Heating is preferable as a dissolving condition. The heating temperature is not particularly limited, but the lower limit may be 30°C, 40°C, 50°C, 60°C, etc.
[0049] The amount of metal silicon to be dissolved is preferably 17%, 15%, or 10% in terms of oxide based on the total mass, and the lower limit is preferably 1%, 3%, or 5%. These upper and lower limits can be combined in any desired manner.
[0050] The basic substance is the same as the basic substance described above. The second basic substance is not particularly limited, but is preferably an organic substance. Examples of the second basic substance include dialkylamines (e.g., those having 1 to 3 carbon atoms) and trialkylamines (e.g., those having 1 to 3 carbon atoms). The total concentration of the basic substance and the second basic substance in the aqueous solution containing the basic substance and / or the second basic substance is not particularly limited. When the basic substance is added, the concentration is preferably such that the amount of the basic substance present is equal to or less than the appropriate amount when the raw solution is finally prepared.
[0051] (hydrothermal treatment process) The hydrothermal treatment step is a step in which the dispersion medium of the dispersion liquid obtained in the raw silica particle preparation step is replaced with water, and then the dispersion liquid is heated to proceed with a hydrothermal reaction. The hydrothermal reaction is preferably carried out at a temperature of 130° C. or higher and 250° C. or lower. In particular, it is preferable to adopt a lower limit of 100° C., 110° C., or 120° C., and an upper limit of 220° C., 200° C., or 180° C. These upper and lower limits can be combined arbitrarily.
[0052] The hydrothermal reaction forms voids inside the spherical silica particles that are finally produced. In other words, the hydrothermal process causes a reaction in which the parts of the particle with low silanol bond density inside the particle are dissolved by a basic substance, and a reaction in which the particle shell is densified by heat, occurring in equilibrium, and it is presumed that the voids formed inside the particle can be controlled by the balance between these two reactions.
[0053] (Heating process) The heating step is a step of heating the raw silica particles contained in the dispersion liquid obtained in the hydrothermal treatment step to form spherical silica particles, and is a step of removing moisture and organic matter contained in the raw silica particles by heating.
[0054] The heating step is performed by heating the dispersion as it is, the dispersion medium of which has been replaced with another dispersion medium, and / or the raw silica particles from the dispersion after solid-liquid separation. The raw silica particles can be separated from the dispersion medium by centrifugation or filtration. After separating the raw silica particles, the dispersion medium can be replaced by adding another dispersion medium such as water or an organic solvent. By replacing the dispersion medium multiple times, organic substances contained in the dispersion can be removed more reliably.
[0055] In the heating step, moisture and organic matter contained in the raw silica particles can be removed by heating at a high temperature. First, it is preferable to remove moisture and organic solvents at a temperature at which moisture is not rapidly removed. For example, 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, etc. Heating can be performed simultaneously with decompression or air drying. If moisture can be removed to a certain extent, even if heated at a high temperature, moisture will not rapidly expand, so the material is heated to a temperature at which organic matter can be removed. Temperatures of 500°C or higher are preferable as temperatures at which organic matter can be removed. In particular, heating in an oxidizing atmosphere such as air is preferable because organic matter can be oxidized and removed. As the lower limit of the heating temperature, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc. can be adopted, and as the upper limit, 1150°C, 1100°C, 1050°C, etc. can be adopted. It is considered that the particles shrink and become dense as moisture is removed by heating the raw silica particles in a state separated from the dispersion medium. In particular, heating to 900°C or higher can strengthen hollow particles and porous particles.
[0056] (Other processes) In the method for producing spherical silica particles according to the present embodiment, the obtained spherical particles can be crushed or surface-treated. Crushing can be performed by a method similar to a normal grinding operation. In particular, it is preferable to use a jet mill or the like.
[0057] The spherical silica particles produced by the method for producing spherical silica particles of this embodiment can be surface-treated with a surface treatment agent such as a silane compound. The appropriate surface treatment varies depending on the form of use of the spherical silica particles. When filling the spherical silica particles in a resin, it is preferable to use a surface treatment agent that can introduce a functional group that has high affinity or reactivity with the resin. EXAMPLES
[0058] The method for producing spherical silica particles of the present invention will be described in detail below with reference to examples.
[0059] <Sample preparation> Test samples for each test example were prepared under the conditions shown in Table 1. The details are explained below. Test Example 1 (Raw material silica particle preparation process) First, an alkaline silicic acid aqueous solution was prepared by mixing 9.0 g of metallic silicon powder (volume average particle size 20 μm), 27.0 g of ion-exchanged water, and 64.0 g of a 25 mass% TMAH aqueous solution, and then keeping the mixture at 40° C. for 48 hours to dissolve the metallic silicon, thereby obtaining an alkaline silicic acid aqueous solution containing approximately 26.3% silicic acid in terms of silica.
[0060] Ion-exchanged water was added to the obtained alkaline silicic acid aqueous solution so that the silicic acid concentration was 4.5 mass% in terms of silica. TMAH was added so that the amount of TMAH present as a basic substance was 0.44 in total molar ratio based on the silicon element derived from the contained silicic acid. Then, acetone was added so that the molar ratio when mixed with water containing the organic solvent was 30.6. Specifically, the ratio of water:acetone was 20:80 in mass ratio before mixing.
[0061] After thorough stirring, a 90% by mass aqueous solution of acetic acid was added to adjust the pH to 8, and stirring was continued for an additional 30 minutes, causing the raw silica particles to precipitate and become a dispersion.
[0062] (Heating process) The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation to separate the precipitate. Centrifugation was performed using Model 3700 manufactured by KUBOTA. The same mass of ion-exchanged water as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes. Centrifugation was performed again under the above conditions, and the obtained precipitate was dried at 130 ° C for 1 hour and then fired at 500 ° C for 2 hours. The obtained fired product was crushed using a mortar until the aggregates could no longer be seen, and the obtained spherical silica particles were used as the test sample of this test example. In Test Example 1, the dispersion obtained in the raw silica particle preparation process was directly subjected to the heating process, and the hydrothermal treatment process was not performed.
[0063] Test Examples 2 and 3 Test samples of these test examples were obtained by carrying out the same operations as in Test Example 1, except that the firing temperature was 800° C. (Test Example 2) and 1000° C. (Test Example 3).
[0064] Test Example 4 A test sample of this test example was obtained in the same manner as in Test Example 3, except that a hydrothermal treatment step was adopted for the dispersion obtained in the raw silica particle preparation step.
[0065] The hydrothermal treatment step was carried out as follows. The dispersion obtained in the raw silica particle preparation step was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation to separate the precipitate. Centrifugation was carried out using a Model 3700 manufactured by KUBOTA. Ion-exchanged water of the same mass as the removed supernatant was added and ultrasonic dispersion was carried out. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes. The obtained dispersion was placed in a pressure vessel and subjected to a hydrothermal reaction at 175°C for 2 hours.
[0066] Test Example 5 A test sample for this test example was obtained in the same manner as in Test Example 4, except that the amount of the basic substance present was 0.79 in molar ratio based on the silicon element derived from silicic acid.
[0067] Test Examples 6-10 A test sample of this test example was obtained in the same manner as in Test Example 4, except for the following differences. a) the amount of basic substance present was set to a molar ratio of 0.55 (Test Examples 6 to 9) or 0.35 (Test Example 10) based on the silicon element derived from silicic acid; b) the hydrothermal treatment temperature was set to 150°C (Test Example 6), 121°C (Test Example 7), or unchanged at 175°C (Test Examples 8 to 10); and c) the firing temperature in the heating step was set to 800°C (Test Example 8) or unchanged at 1000°C (Test Examples 6, 7, 9, 10).
[0068] Test Example 11 (Equivalent to the raw silica particle preparation process) A mixture of 5.2g of TEOS, 100g of ion-exchanged water, and 400g of acetone was prepared. 2.5g of 25% by mass TMAH aqueous solution was added to this mixture while stirring. Then, 90% by mass acetic acid aqueous solution was quickly added to adjust the pH to 8, and stirring was continued for another 30 minutes, causing the raw silica particles to precipitate and become a dispersion. The ratio of ion-exchanged water to acetone was set so that the relative dielectric constant was 30.6. The amount of TMAH added was 1.0g, which is the amount of TMAH derived from TEOS. Noke The molar ratio was set to 0.27 based on elemental iron.
[0069] (corresponding to the hydrothermal treatment process) The obtained dispersion was centrifuged at 5000 rpm for 5 minutes, and the supernatant was removed by decantation to separate the precipitate. Centrifugation was performed using a KUBOTA Model 3700. Ion-exchanged water of the same mass as the removed supernatant was added and ultrasonic dispersion was performed. Ultrasonic waves were applied at a frequency of 28 kHz and 1000 W for 30 minutes. The obtained dispersion was placed in a pressure vessel and subjected to a hydrothermal reaction at 175°C for 2 hours.
[0070] (corresponding to the heating process) Then, the mixture was centrifuged again under the above conditions, and the resulting precipitate was dried at 130° C. for 1 hour, and then calcined at 1000° C. for 2 hours. The calcined product was crushed in a mortar until agglomerates could no longer be seen with the naked eye, and the resulting spherical silica particles were used as the test sample for this test example.
[0071] Test Example 12 The same operation as in Test Example 3 was carried out, except that the content of acetone was set to an amount that would be 20 when mixed with the water contained. As a result, no particle generation was observed in the process corresponding to the raw silica particle preparation process, and no heating process was performed. Therefore, no test sample for this test example was obtained.
[0072] Test Example 13 The same procedure as in Test Example 1 was carried out, except that the content of acetone was set to an amount that would become 41.5 when mixed with the contained water. In the raw silica particle preparation step, spherical particles were not produced, and only aggregates were obtained.
[0073] Test Example 14 The same operation as in Test Example 1 was performed, except that the amount of the basic substance present was set to 0.20 in molar ratio based on the silicon element derived from silicic acid. In the raw silica particle preparation step, spherical particles were not produced, and only aggregates were obtained.
[0074] Test Example 15 The same operation as in Test Example 1 was carried out, except that the amount of basic substance present was set to 0.85 in molar ratio based on the silicon element derived from silicic acid. As a result, no particle generation was observed in the process corresponding to the raw silica particle preparation process, and no heating process was carried out. Therefore, no test sample for this Test Example was obtained.
[0075] Test Examples 16 and 17 The test samples of this test example were obtained by the same procedure as in Test Example 4, except that the amount of basic substance present was 0.35 (Test Example 16) or 0.54 (Test Example 17) in molar ratio based on the silicon element derived from silicic acid.
[0076] Test Examples 18 and 19 Test samples of this Test Example were obtained by the same procedure as Test Example 4, except that DBU (Test Example 18) and DBN (Test Example 19) were used instead of TMAH as the basic substance. The amounts of DBU and DBN added were the same as those of TMAH. As a result, the amounts of DBU and DBN added were adjusted so that the amount of basic substance present was 0.41 in molar ratio based on the silicon element derived from silicic acid.
[0077] Test Examples 20 and 21 Test samples of this test example were obtained by the same procedure as in Test Example 4, except that TEAH (Test Example 20) and TBAOH (Test Example 21) were used instead of TMAH as the basic substance. The amounts of TEAH and TBAOH added were adjusted to have the same concentrations as TMAH. As a result, the amounts of TEAH and TBAOH added were adjusted so that the amount of basic substance present was 0.32 (Test Example 20) and 0.35 (Test Example 21) in molar ratio based on silicon element derived from silicic acid.
[0078] Test Example 22 We used CellSpheres manufactured by Taiheiyo Cement Corporation as is. CellSpheres are spherical particles made of alumina borosilicate glass with a hollow structure and a particle size of 10 μm or less.
[0079] Test Example 23 The hollow silica particles were prepared as described in Example 8 of Patent Document 2. Specifically, the hollow silica particles were prepared based on the description in paragraphs 0088 to 0093 of Patent Document 2. The obtained hollow silica particles had a volume average particle size of 0.5 μm.
[0080] Test Example 24 The metallic silicon powder used to prepare the alkaline silicic acid aqueous solution in the raw silica particle preparation step of Test Example 9 was dispersed in air as a carrier gas and introduced into a high-temperature oxidizing atmosphere to deflagrate and then rapidly cooled, a so-called VMC method, to produce spherical silica particles, which were used as the test sample of this Test Example. The impurity contents of the test sample of this Test Example and the test sample of Test Example 9 were measured. The results are shown in Table 2.
[0081] (evaluation) The test samples of each test example were measured for particle size distribution, specific surface area, pore volume, true specific gravity, and coarse particle evaluation. The results are shown in Table 1.
[0082] Particle size distribution: The test sample was dispersed in water at a concentration of 0.5% by mass, and the particle size distribution was measured using a particle size distribution measuring device (Shimadzu SALD-7500 nano). For Test Examples 4, 5, 9, and 11, the histograms of the measured particle size distribution are shown in Figure 1.
[0083] Ratio of particles with coarse internal voids: The ratio of particles with coarse internal voids was measured for the test samples of Test Examples 11, 17, 22, and 23, and is shown in Table 3. Coarse internal voids are those with a major axis that is 50% or more of the particle diameter (major axis) of the spherical silica particles.
[0084] The long diameter of the internal voids and the long diameter of the particles were measured on a cross section cut from spherical silica particles embedded in resin. First, liquid epoxy resin (ZX1059) and the test sample were mixed, and then an appropriate amount of hardener (Ethacure 100) was added and mixed, and the mixture was heated to 170°C to harden. The resulting hardened resin was cut and the cross section polished. The surface was then treated with an ion milling device (Hitachi High-Tech), osmium coated, and SEM photographs were taken.
[0085] Ten particles were randomly selected from those appearing in this cross section, and the longest diameter of the cut surface of the particle was designated as the longest diameter A of the particle, and the longest longest diameter of the cross section of the internal void appearing in the cross section was designated as B. The proportion of particles for which B / A was 0.5 or more was calculated.
[0086] Internal void distribution in particles: For the test samples of test examples 11, 17, 22, and 23, the test samples of each test example were embedded in resin and cut in the same manner as in the coarse internal void particle ratio test described above, and the void distribution state (percentage of void area) on the cut surface was evaluated and is shown in Table 3.
[0087] As mentioned above, the cross-section image with the largest cross-section area was selected from multiple cross-section images obtained in 10 nm steps by FIB / SEM as the evaluation cross-section image. Then, the void area ratio in the central region (a circular region with half the radius from the center of the cross-section) and the void area ratio in the outer shell region (the region of the particle cross-section excluding the central region) were calculated. The area ratio was calculated using image processing software (Azo-kun: manufactured by Asahi Kasei Engineering). This was performed on 10 randomly selected particles, and the average value was calculated.
[0088] Specific surface area, pore volume: The test samples were measured using an automatic specific surface area / pore distribution measuring device (Shimadzu Tristar 3000). The specific surface area was measured by the BET single point method using nitrogen gas. The pore volume was measured using the value at the time of adsorption measured using the BJH method.
[0089] True specific gravity: measured with a dry automatic density meter (Shimadzu Corporation, Accupic II 1345) in nitrogen gas The density was measured using the particle volume including the voids inside the spherical silica particles into which nitrogen gas cannot penetrate. In other words, if voids exist, the density of the spherical silica particles decreases by the volume of the voids.
[0090] Dielectric properties: Using a Keycom device, the relative dielectric constant and dielectric loss tangent were measured at 1 GHz using the cavity resonance method.
[0091] Pressure test: 1.5 g of a test sample was placed in a vacuum pack and degassed, and then pressed at 300 MPa in water for 1 minute using a cold isostatic press (manufactured by Nikkiso). SEM: SEM photographs were taken for each of the test samples of Test Examples 3 to 7, 9, 11, 13, and 16 to 19. TEM: The test sample was embedded in resin and a TEM photograph was taken. First, the test sample was mixed with liquid epoxy resin (ZX1059), and then an appropriate amount of hardener (Ethacure 100) was added and mixed, after which it was heated to 170°C to harden. The hardened resin obtained was cut and the cross section polished. The surface was then treated with an ion milling device (Hitachi High-Tech), and an osmium coat was applied before a TEM photograph was taken (Figure 7). SEM: The same processing as that performed in the TEM described above was performed and SEM photographs were taken.
[0092] [Table 1]
[0093] As is clear from Table 1, in Test Examples 4 to 10 and 16 to 21, which include a hydrothermal treatment step, the true specific gravity measured with nitrogen gas was 2.3 g / cm 3 or lower than the true specific gravity measured with helium gas. 3 ), revealing the presence of voids inside the particles. In contrast, for Test Example 3, which did not undergo the hydrothermal treatment step, both the true density measured with nitrogen gas and the true density measured with helium gas were 2.3 g / cm, which is roughly consistent with the true density of silica. 3It was found that there were no internal voids. It was therefore found that the hydrothermal treatment process can effectively form spherical silica particles (hollow particles) with internal voids. When observing the SEM photographs, almost no pores were observed on the surface, or only a few pores were observed. In addition, as is clear from the SEM photographs, the particle sizes of these test samples were non-uniform, and the particle size distribution shown in Figure 1 also makes it clear that the particle sizes were non-uniform.
[0094] Test Examples 1 to 3, 8 and 9 are hollow particles obtained by processing under the same conditions except for the firing temperature within each group. It was found that the pore volume changes by changing the firing temperature.
[0095] Test Examples 6, 7, and 9 are hollow particles obtained under the same conditions except for the treatment temperature in the hydrothermal treatment step. It was found that the particle size distribution and pore volume values can be changed by changing the hydrothermal treatment conditions. In particular, the voids formed inside the particles can be controlled by changing the temperature in the hydrothermal treatment. For example, when the temperature in the hydrothermal treatment step is low, the volume of pores communicating with the outside tends to increase.
[0096] Test Examples 4, 12, and 13 are spherical silica particles obtained under the same conditions except for the relative dielectric constant of the mixed solvent of water and an organic solvent. It was found that when the relative dielectric constant of the mixed solvent was 20 (Test Example 12) or 41.5 (Test Example 13), spherical silica particles could not be obtained. Specifically, in Test Example 12, which has a low relative dielectric constant, no precipitation occurred and therefore no particulation occurred, while in Test Example 13, as is clear from Figure 9, only aggregates were obtained. This shows that the relative dielectric constant of the mixed solvent is required to be greater than 20 and less than 41.5.
[0097] Test Examples 4, 5, 9, 10, and 14 to 17 are spherical silica particles obtained under the same conditions except for the amount of basic substance. It was found that when the amount of basic substance added is 0.20 (Test Example 14) or 0.85 (Test Example 15) in terms of molar ratio based on silicon element derived from silicic acid, spherical silica particles themselves cannot be obtained. Here, in Test Example 14, where the amount of basic substance added is small, only aggregates are formed, and in Test Example 15, where the amount of basic substance added is large, no precipitate is formed and no particulation is formed, and it was found that the amount of basic substance added must be more than 0.20 and less than 0.85 in terms of molar ratio based on silicon element derived from silicic acid.
[0098] In Test Example 11, raw silica particles were prepared using TEOS in the raw silica particle preparation process, and therefore D90 / D10 was a small value of 1.76, and it was revealed that the particle size of the obtained hollow particles was uniform (Figures 1 and 8). In contrast, in Test Examples 1 to 10 and 16 to 21, in which raw silica particles were prepared using metal silicon powder in the raw silica particle preparation process, even the smallest Test Example 10 had a D90 / D10 of 2.78, and it was found that hollow particles with non-uniform particle sizes were obtained (Figures 1 to 7, 10 to 13). Non-uniform particle sizes have the advantage of improving the filling properties of hollow particles in resin compositions and slurry compositions.
[0099] In Test Examples 4 and 18 to 21, hollow particles were obtained under the same conditions except for changing the type of basic substance. It was revealed that spherical silica particles could be prepared without any problems even if the basic substance was changed to these substances.
[0100] Test Examples 3, 9, 11, 16 to 18, 22, and 23, in which the dielectric loss tangent was measured, all showed very small values of the dielectric loss tangent. Test Examples 11, 17, 22, and 23 among them were subjected to a pressurization test at 300 MPa, and the true specific gravity and dielectric loss tangent measured with nitrogen gas before and after the test were measured. As a result, Test Examples 11, 17, and 23 all had high true specific gravity retention rates of 84% (Test Example 11), 100% (Test Example 17), and 86% (Test Example 13), while Test Example 22 had a retention rate of 0%, indicating that almost all of the hollow structure had been destroyed. In addition, Test Example 23 showed a very high dielectric loss tangent retention rate of 600%, while Test Example 16 showed a very low retention rate of 171%, and Test Example 17 showed a very low retention rate of 268%. A high dielectric loss tangent retention rate indicates that a large number of voids have been destroyed or that there are components inside the voids that increase the dielectric loss tangent; in either case, it suggests that a high proportion of voids have been destroyed.
[0101] The resistance to destruction by these pressure tests can also be seen from cross-sectional SEM and TEM photographs. In Test Examples 11 and 17, the outer shell of the particle is composed of a dense structure, and it can be observed from the cross-sectional SEM photographs that multiple fine voids are formed near the center (Figures 15 and 16). In addition, it can be observed from the TEM photographs that the density of the test sample of Test Example 17 gradually decreases near the center, and it can be inferred that fine voids are formed near the center (Figure 14). In this way, it can be inferred that the fine voids are difficult to destroy even when an external force is applied, and that the destruction of the internal voids did not progress very much even during the pressure test. In contrast, in Test Examples 22 and 23, the internal voids were large, and it is inferred that the destruction of the voids progressed due to the pressure test (Figures 17 and 18).
[0102] [Table 2]
[0103] As is clear from Table 2, even though the silica particles were produced from the same metal silicon powder, the impurity concentration was lower in the test sample of Test Example 24 produced by the method of the present invention. This is presumably because, in Test Example 24, the metal silicon powder was directly oxidized to form silica, whereas in Test Example 9, the metal silicon powder was first dissolved and then silica was precipitated, so that no impurities were taken in during precipitation, allowing the impurity content to be reduced.
[0104] [Table 3]
[0105] As is clear from Table 3, in the test sample of Test Example 17, which falls within the scope of the present invention, there were no particles with internal voids that were more than half the particle size, and it was further revealed that the voids consisted of multiple voids and were concentrated in the central region.
[0106] In contrast, in the commercially available test samples of Test Examples 22 and 23, all particles had voids equal to or greater than half the particle size, and the central regions of the particles remained voids. Furthermore, it was found that the voids in the central regions were large enough to extend to the outer shell regions.
[0107] In Test Example 11 prepared from TEOS, many of the voids were relatively large, and it was found that the ratio of coarse internal void particles was high at 70%.
[0108] As a result, it was found that the true specific gravity maintenance rate of Test Example 17 was 91%, and the destruction of voids was suppressed, while Test Example 11 was 84%, Test Example 22 was 0%, and Test Example 23 was 86%. In addition, it was found that the dielectric tangent maintenance rate of Test Example 23 was high at 600%, while the test sample of Test Example 17 showed a low value of 268%.
[0109] (Other exams) In the above test examples, metallic silicon powder was used as the raw material for preparing the alkaline silicic acid aqueous solution, but it was confirmed that spherical silica particles could also be produced by using other materials, such as silica particles and water glass (aqueous sodium silicate solution).After preparing the alkaline silicic acid aqueous solution from each of the materials, silica and sodium silicate aqueous solution, the same spherical silica particles as those using metallic silicon powder could be obtained by carrying out the same operations as those using metallic silicon powder.
[0110] -Method using silica particles 20.0 g of silica powder (product name: SO-E2, manufactured by Admatechs Co., Ltd.), 15.0 g of ion-exchanged water, and 64.0 g of a 25% by mass TMAH aqueous solution were mixed and held at 180°C for 1 hour in a pressure vessel to dissolve the silica, thereby obtaining an alkaline silicic acid aqueous solution containing approximately 20.2% silicic acid in terms of silica.
[0111] Method using sodium silicate solution 10.2 g of sodium silicate aqueous solution (water glass) and 15.0 g of ion-exchanged water were mixed and stirred at 40° C. for 4 hours. Then, 64.0 g of 25% by mass TMAH aqueous solution was added dropwise to remove Na ions by ion exchange. As a result, an alkaline silicic acid aqueous solution containing 10.8% by mass of silica was obtained.
Claims
1. The average particle size is 0.1 to 10.0 μm, True specific gravity measured with nitrogen gas is 0.9 to 1.9 g / cm 3 , Pore volume is 0.1 mL / g or less; Na content is 10 ppm or less, Before and after applying pressure of 300 MPa for 1 minute, the true specific gravity retention rate measured with nitrogen gas is 80% or more. The ratio of particles having an internal void with a maximum major axis that is equal to or greater than half the major axis of each particle is 60% or less; Spherical silica particles whose main component is silica.
2. A spherical silica particle as described in claim 1, wherein the average porosity of the central region in the particle cross section is 5% or more and 90% or less, and the average porosity of the remaining region, the outer shell region, is less than the average porosity of the central region and is 2% or more and 80% or less.
3. 3. The spherical silica particles according to claim 1, having a dielectric loss tangent retention rate of 500% or less.
4. 3. The spherical silica particles according to claim 1, wherein D90 / D10 is from 2.0 to 20.
0.
5. The true specific gravity measured with helium gas is 2.2 g / cm 3 The spherical silica particles according to claim 1 or 2.
6. 3. The spherical silica particle according to claim 1, wherein an organic functional group is introduced onto the surface of the particle.
7. The spherical silica particles according to claim 1 or 2, A dispersion medium for dispersing the spherical silica particles; 1. A slurry composition comprising:
8. The spherical silica particles according to claim 1 or 2, A resin material in which the spherical silica particles are dispersed; The resin composition has the formula:
9. a raw silica particle preparation step of preparing a dispersion of raw silica particles from a raw material solution in which silicic acid is dissolved in a mixed solvent of water and an organic solvent in the presence of a basic substance consisting of at least one of a quaternary ammonium salt and a base having a cyclic amidine structure; a hydrothermal treatment step of replacing the dispersion medium for dispersing the raw silica particles in the dispersion with water, and then pressurizing and heating the mixture to 130° C. or higher and 250° C. or lower to obtain a dispersion of hydrothermally treated raw silica particles; a heating step of heating the dispersion liquid or the raw silica particles obtained by solid-liquid separation from the dispersion liquid after the hydrothermal treatment step to remove organic matter contained in the dispersion liquid and prepare spherical silica particles; having The mixed solvent has a relative dielectric constant of 21 or more and 40 or less, A method for producing spherical silica particles, wherein the basic substance is mixed in a molar ratio of 0.3 or more and 0.8 or less with respect to the silicon element derived from the silicic acid.
10. The method for producing spherical silica particles according to claim 9, wherein the organic solvent is one or more solvents selected from the group consisting of acetone, methyl ethyl ketone, and ethyl acetate.
11. The method for producing spherical silica particles according to claim 9 or 10, wherein the basic substance is at least one compound selected from the group consisting of quaternary ammonium having 4 to 16 carbon atoms, diazabicycloundecene, and diazabicyclononene.
12. The method for producing spherical silica particles according to claim 9 or 10, wherein the heating step is performed at 900° C. or higher.
Citation Information
Patent Citations
Silicon dioxde acetone dispersion liquor and its preparation method
CN1800012A
Method for producing spherical silica-based mesoporous body
JP2006027985A
Method for manufacturing anisotropic-shape silica sol
JP2007153671A
Porous silica particle and producing method of the same
JP2010138021A
Inorganic hollow powder, method for producing the same and application of the hollow powder
JP2010260755A